Model construction and verification of a BLDC motor using MATLAB/SIMULINK and FPGA control - Ming-Fa Tsai; Tran Phu Quy; Bo-Feng Wu; Chung-Shi Tseng (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
This paper presents the model construction of a brushless DC motor via MATLAB/SIMULINK and FPGA control, so that one can evaluate the performance of the BLDC motor control with various control schemes using MATLAB/SIMULINK. The constructed model consists of a BLDC motor dynamics block, a Hall-sensor signals generation block, a back-emf block, and a PWM-generation logic block. In order to evaluate the model, various cases of simulation studies are carried out. The control and PWM-generation logic block then can be transferred to digital hardware circuit in VHDL hardware description language for co-simulation verification in the MATLAB/SIMULINK and ModelSim environment. Experiment results by using FPGA control are also obtained to verify the correctness of the constructed BLDC model.